Confucian political theory and the problem of moral luck: in defence of holistic sufficientarianism - Chua, Jonathan Yi (Nanyang Technological University, 2023)
Early Confucian philosophers assert that people have the same moral capacity to develop themselves into sages. On paper, their belief in the formal equality of moral potential provides a fair baseline for evaluating a person’s ethical merit. Ethical merit, in turn, serves as the primary criterion for the just distribution of social and political positions, which is one of the central features of most contemporary Confucian political theories.